Clinical value of procalcitonin-to-albumin ratio for identifying sepsis in neonates with pneumonia. (31st December 2023) - Li, Tiewei; Li, Xiaojuan; Zhu, Zhiwei; Liu, Xinrui; Dong, Geng; Xu, Zhe; Zhang, Min; Zhou, Ying; Yang, Jianwei; Yang, Junmei; Fang, Panpan; Qiao, Xiaoliang
Abstract: Background: It is possible that neonates with pneumonia also have unrecognized sepsis. Identifying sepsis in neonates with pneumonia may cause some trouble for clinicians. This study aimed to evaluate the clinical value of the procalcitonin-to-albumin ratio (PAR) in identifying sepsis in neonates with pneumonia. Methods: We retrospectively included 912 neonates with pneumonia from January 2016 to July 2021. Clinical and laboratory data were collected from electronic medical records. Among neonates with pneumonia, 561 neonates were diagnosed with sepsis, according to the International Pediatric Sepsis Consensus. Neonates were divided into a sepsis group and a pneumonia group. A multivariate logistic regression analysis was used to evaluate whether PAR was a potential independent indicator for identifying sepsis in neonates with pneumonia. Receiver operating characteristic (ROC) curve analysis was performed to evaluate the diagnostic value of PAR in sepsis. Results: Neonates with sepsis have a higher PAR ( p < 0.001). Correlation analysis showed that PAR was positively correlated with the level of C-reactive protein ( r = 0.446, p < 0.001). Multiple logistic regression analysis showed that PAR was an independent predictor of the presence of sepsis in neonates with pneumonia. ROC curve analysis revealed that PAR had good power in identifying sepsis in neonates with pneumonia (area under curve (AUC) = 0.72, 95% confidence interval (CI), 0.68-0.75, p < 0.001). Conclusion: PAR can be used as a new biomarker to identify sepsis in neonates with pneumonia. Key Messages: Compared with neonates with pneumonia, neonates with both pneumonia and sepsis had a higher PAR. PAR was a useful biomarker in distinguishing septic neonates from neonates with pneumonia.